Approaches to identifying stakeholders in environmental management: Insights from practitioners to go beyond the 'usual suspects'. (March 2016) - Colvin, R.M.; Witt, G. Bradd; Lacey, Justine
Graphical abstract: Highlights: We interviewed ENRM engagement practitioners about identification of stakeholders. We categorise the 'art' and 'science' of approaches to stakeholder identification. We outline operational definitions of 'stakeholder', 'community', and 'citizenry'. We discuss how status as a stakeholder is awarded in ENRM. Abstract: Stakeholder analysis and engagement processes are recognised as essential in environmental and natural resources management (ENRM). Underpinning these processes is the identification of stakeholders, an often tacit process which finds the practitioner responsible for stakeholder analysis or engagement sifting through all of society to determine who is awarded stakeholder status for the given project or issue. While the ENRM literature provides guidance for stakeholder analysis and engagement, there has not been the same level of examination of the practical approaches to—and assumptions underlying—stakeholder identification by practitioners working in the field. This research extends on the ENRM stakeholder analysis and engagement literature by exploring the approaches to identification as used by ENRM practitioners. Semi-structured interviews ( n = 20) were conducted with ENRM practitioners, leading to the classification of eight approaches to stakeholder identification. These approaches are discussed as the 'art' and 'science' of stakeholder identification. Practitioners' conceptualisations of the terms stakeholder, community, and the citizenry are discussed, and differences in understandings of these critical terms are outlined based on the broad domain of ENRM in which the practitioner is operating (land use change versus agricultural extension or community engagement). The social structures of relevance to stakeholder identification (individual, social constituency, group, organisation) are presented, and practitioners' perspectives on the role of groups are discussed. Through explicating the approaches to identification of stakeholders, this research offers new perspectives on a significant element of ENRM. These insights provide greater clarity on the practices which shape stakeholder analysis and engagement in ENRM, and highlight the importance of acknowledging the privileged position of the practitioner in deciding who is awarded stakeholder status in a project or issue.